Hubungan Perilaku Higiene dengan Kejadian Diare pada Siswa SD Negeri 01 Trangsan Kecamatan Gatak Kabupaten Sukoharjo - Sutanto, Sutanto, Badar Kirwono, SKM, M.Kes, Yuli Kusumawati, SKM,M.Kes (Epid) (2017)
Diarrhea is a disease that is still a public health problem in developing countries including Indonesia are closely related to the quality of individual environmental sanitation and clean living healthy behavior. The purpose of this research is to know the behavior of the facility's relationship with incidence of diarrhea in students "SDN 01 Trangsan Kecamatan Gatak Kabupaten Sukoharjo". Research conducted with observational approach that uses cross sectional. The selection of the sample by proportional random sampling as much as 97 students. Using the chi square statistical tests using computer programs. The results showed that 61.9% bowel habits are already good, handwashing habits with categories less well of 38,1%, customs cut nails already good of 72,6%, often spending habits of 69.6% (p = 0,065) which means there is no relation between incidence of diarrhea with spending habits.